The pre-vascularisation of a collagen-chondroitin sulphate scaffold using human amniotic fluid-derived stem cells to enhance and stabilise endothelial cell-mediated vessel formation. (15th October 2015) - Lloyd-Griffith, Cai; McFadden, Tara M.; Duffy, Garry P.; Unger, Ronald E.; Kirkpatrick, C. James; O'Brien, Fergal J.
Graphical abstract: Abstract: A major problem in tissue engineering (TE) is graft failure in vivo due to core degradation in in vitro engineered constructs designed to regenerate thick tissues such as bone. The integration of constructs post-implantation relies on the rapid formation of functional vasculature. A recent approach to overcome core degradation focuses on the creation of cell-based, pre-engineered vasculature formed within the TE construct in vitro, prior to implantation in vivo . The primary objective of this study was to investigate whether an amniotic fluid-derived stem cell (AFSC)–human umbilical vein endothelial cell (HUVEC) co-culture could be used to engineer in vitro vasculature in a collagen chondroitin sulphate (CCS) scaffold. The secondary objective was to investigate whether hypoxic conditions (2% O2 ) could enhance microcapillary-like structure formation by this co-culture. The results of this study demonstrate, for the first time, that the AFSC–HUVEC co-culture was capable of pre-vascularising CCS scaffolds within 7 days and that the AFSCs are capable of behaving as pericytes while interacting with HUVECS to form microcapillary-like structures. However, this microcapillary-like structure formation was reduced in hypoxic conditions. qRT-PCR analysis indicated that an upregulation of VEGFR1 and accompanying decrease of VEGFR2 gene expression may be responsible for the poor response of these microcapillary-like structures to hypoxic conditions. Overall, however, these results demonstrate the potential of this newly developed co-culture system for the formation of pre-engineered vasculature within TE constructs. Statement of Significance: This article describes the development of an amniotic fluid-derived stem cell (AFSC)–human umbilical vein endothelial cell (HUVEC) co-culture for use in engineering in vitro vasculature in a collagen chondroitin sulphate (CCS) scaffold. The article also describes the effect of hypoxic conditions on the networks of microcapillary-like structures formed by this co-culture. The AFSC–HUVEC co-culture was capable of pre-vascularising CCS scaffolds within 7 days. However, microcapillary-like structure formation was reduced in hypoxic conditions. Overall, these results demonstrate the potential of this newly developed co-culture system for the formation of pre-engineered vasculature within TE constructs. The proangiogenic nature of this co-culture has the potential to both enhance bone regeneration while also overcoming the problem of inadequate vascularisation of grafts commonly seen in the field of tissue engineering.